Chenodeoxycholic Acid Improves Embryo Implantation and Metabolic Health through Modulating Gut Microbiota-Host Metabolites Interaction during Early Pregnancy - Meixia Chen; Ying Zhao; Haifeng Ji; Lu Li; Hui Liu; Sixin Wang; Dongyan Zhang; Jingdong Yin; Jing Wang; Xin Zhang (MDPI AG, 2023)
Fetus loss in early pregnancy is of major concern to both humans and animals, and this issue is largely influenced by embryo implantation. Chenodeoxycholic acid (CDCA), a primary bile acid, contributes to metabolic improvements and protects against intrahepatic cholestasis of pregnancy. However, the effect of CDCA on embryo implantation during early pregnancy has not been investigated. The present study demonstrated that CDCA administration during early pregnancy improved embryo implantation in sows and rats, thereby improving the pregnancy outcomes of sows. CDCA significantly reduced inflammation, oxidative stress, and insulin resistance. The metabolomics analysis indicated significant differences in the fecal metabolome, especially regarding the level of secondary bile acids, between the control and CDCA-treated sows. CDCA also influenced the serum metabolite profiles in sows, and the serum L-Histidine level was significantly correlated with the abundance of 19 differential fecal metabolites. Importantly, L-Histidine administration improved embryo implantation and metabolic health in rats during early pregnancy. Moreover, CDCA administration during early pregnancy also led to long-term metabolic improvements in sows. Our data indicated that CDCA improved embryo implantation by alleviating inflammation and oxidative stress, improving insulin sensitivity, and modulating the interaction between the gut microbiota and host metabolites. Therefore, CDCA intervention is a potential therapeutic strategy regarding embryo loss during pregnancy.